Imperfect Information and Inflation Expectations: Evidence from Microdata - Michael Lamla; Lena Dräger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate the updating behavior of individual consumers regarding their short- and long-run inflation expectations. Utilizing the University of Michigan Survey of Consumer's rotating panel microstructure, we can identify whether individuals adjust their inflation expectations over a period of six months. We find evidence that the updating frequency has been underestimated. Furthermore, looking at the possible determinants of an update we find support for imperfect information models. Moreover, individual expectations are found to be more accurate after an update and forecast accuracy is affected by inflation volatility measures and news regarding inflation. Finally, the updating frequency is found to significantly move spreads in bond markets.
Keywords: D84; E31; E50; 330